SpiderBat: Augmenting wireless sensor networks with distance and angle information - Oberholzer, G; Sommer, P; Wattenhofer, R (2011 10th International Conference on Information Processing in Sensor Networks, 2011)
Having access to accurate position information is a key requirement for many wireless sensor network applications. We present the design, implementation and evaluation of SpiderBat, an ultrasound-based ranging platform designed to augment existing sensor nodes with distance and angle information. SpiderBat features independently controllable ultrasound transmitters and receivers, in all directions of the compass. Using a digital compass, nodes can learn about their orientation, and combine this information with distance and angle measurements using ultrasound. To the best of our knowledge, SpiderBat is the first ultrasound-based sensor node platform that can measure absolute angles between sensor nodes accurately. The availability of angle information enables us to estimate node positions with a precision in the order of a few centimeters. Moreover, our system allows to position nodes in multi-hop networks where pure distance-based algorithms must fail, in particular in sparse networks, with only a single anchor node. Furthermore, information on absolute node orientations makes it possible to detect whether two nodes are in line-of-sight. Consequently, we can detect the presence of obstacles and walls by looking at patterns in the received ultrasound signal.